2018
DOI: 10.1371/journal.pone.0192152
|View full text |Cite
|
Sign up to set email alerts
|

Body size estimation of self and others in females varying in BMI

Abstract: Previous literature suggests that a disturbed ability to accurately identify own body size may contribute to overweight. Here, we investigated the influence of personal body size, indexed by body mass index (BMI), on body size estimation in a non-clinical population of females varying in BMI. We attempted to disentangle general biases in body size estimates and attitudinal influences by manipulating whether participants believed the body stimuli (personalized avatars with realistic weight variations) represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 55 publications
7
51
0
Order By: Relevance
“…More sophisticated 3D scanning systems have also been used to create personalized avatars, for research on body perception (Piryankova et al, 2014a;Mölbert et al, 2017a;Thaler et al, 2018), and on attitudes toward using 3D body scanning for clothing customization and selection (Lee et al, 2012). The scanning systems are capable of capturing both the shape and the texture of the body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More sophisticated 3D scanning systems have also been used to create personalized avatars, for research on body perception (Piryankova et al, 2014a;Mölbert et al, 2017a;Thaler et al, 2018), and on attitudes toward using 3D body scanning for clothing customization and selection (Lee et al, 2012). The scanning systems are capable of capturing both the shape and the texture of the body.…”
Section: Introductionmentioning
confidence: 99%
“…The focus on women is likely due to the higher prevalence of eating disorders in women, as well as findings suggesting a relationship with distortions of body size perception in these disorders (Thompson et al, 1999). Additionally, healthy females were also found to not accurately estimate their own body weight (Piryankova et al, 2014a;Mölbert et al, 2017a;Thaler et al, 2018). Previous studies found that healthy females in the normal body mass index (BMI) range slightly underestimated their body weight and were more willing to accept thinner bodies as their own as compared to fatter bodies (Piryankova et al, 2014a;Mölbert et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…In metric methods, often also referred to as body part methods, the size of body parts is estimated against a spatial measure (e.g., a caliper or a measure tape) and thus local spatial estimates of body parts are assessed ( Home, Van Vactor, & Emerson, 1991 ; Slade & Russell, 1973 ). In depictive methods, often also referred to as whole body methods, the size and shape of the whole body are compared with another body of self or other identity (e.g., photographs or computer-generated bodies) usually manipulated in body weight ( Mölbert et al., 2018 ; Piryankova et al., 2014 ; Thaler et al., 2018 ; Tovée, Benson, Emery, Mason, & Cohen-Tovée, 2003 ). A recent review suggests that healthy people on average accurately estimate their own bodily dimensions in depictive methods, whereas they overestimate in metric methods ( Mölbert et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the international classification of body weight [11], [15]we investigated the influence of personal body size, indexed by body mass index (BMI, obesity is defined as a BMI of 30 and above, overweight as a BMI between 25 and 29.9, normal weight as a BMI between 18.5 and 24.9, and underweight as a BMI below 18.5.…”
Section: Methodsmentioning
confidence: 99%